Gammaherpesvirus RNAs Come Full Circle - Nathan A. Ungerleider (American Society for Microbiology, 2019)
ABSTRACT After an adaptive immune response is mounted, gammaherpesviruses achieve persistence through the utilization of viral noncoding RNAs to craft a suitable host cell environment in an immunologically transparent manner. While gammaherpesvirus long noncoding RNAs (lncRNAs) and microRNAs have been recognized for some time and have been actively investigated, a recent spate of reports have now identified repertoires of the circular RNA (circRNA) class of noncoding RNAs in both the lymphocryptovirus and rhadinovirus genera of gammaherpesviruses. Despite the recent nature of these findings, the detection of circRNAs across viruses and viral gene expression programs, the conservation of some viral circRNAs, and their detection in the clinical setting already raises the spectrum of functional importance in gammaherpesvirus biology and associated malignancies. Here, we provide an overview of currently known gammaherpesvirus circular RNAs and discuss reported physical and contextual properties that may be germane to future functional studies. With the Epstein-Barr virus (EBV) circRNAome being the most extensively studied to date, our discussions will be weighted toward EBV circRNAs while also addressing circRNAs discovered in the rhesus macaque lymphocryptovirus (rLCV), the Kaposi’s sarcoma herpesvirus (KSHV), and the murid gammaherpesvirus 68 (MHV68). We hope that this will help set the stage for future investigations into the functions and relevance of this new class of viral noncoding RNAs in infection and disease.